Topical N-palmitoyl serinol, a commensal bacterial metabolite, prevents the development of epidermal permeability barrier dysfunction in a murine model of atopic dermatitis-like skin - Wen, Si (Can J Vet Res, 2021)
Recent studies have demonstrated that commensal bacterial metabolites benefit human health. Because of the crucial role of the epidermal permeability barrier in cutaneous and extracutaneous function, we assessed whether the topical applications of N-palmitoyl serinol (NPS) would improve the epidermal permeability barrier in murine skin. Our results show that the topical application of 0.5% NPS in ethanol twice daily for 1 week lowered basal transepidermal water loss rates and accelerated barrier recovery in normal mice. Moreover, topical NPS prevented the emergence of epidermal permeability barrier dysfunction in a murine model of allergic contact dermatitis. These results suggest that topical NPS could be used to prevent or treat skin disorders characterized by inflammation and an abnormal epidermal permeability barrier.